Tindak Tutur Ilokusi Pembeli Di Warung Nasi Uduk Batavia - Revina Prasetyani (PIKTORIAL : Journal of Humanities, 2021)
This research on illocutionary speech acts aims to describe the types of illocutionary speech acts and the mode of sentences of buyers at the Nasi Uduk Batavia shop. The theory used is Searle's deep illocutionary speech act theory (Rohmadi, 2017) and sentence mode (Ramlan, 2005). The research data were collected using the observation and recording method, with the instrument used, namely the researcher himself who became the main instrument and assisted by a recording device, which was then analyzed using the equivalent method and advanced techniques, namely the technique of sorting the determining elements or PUP technique. From the findings of the types of illocutionary speech acts in the speech of sellers and buyers at the Nasi Uduk Batavia shop, 50 data were analyzed. The results of this study indicate that illocutionary speech acts at Nasi Uduk Batavia stalls consist of assertive illocutionary speech acts, directive illocutionary speech acts, expressive illocutionary speech acts, and declarative illocutionary speech acts. the nature of the illocutionary speech act of buying and selling interactions at a Nasi uduk Batavia stall, consisting of: stating, rejecting, ordering, asking, thanking, apologizing, criticizing, deciding. The most dominant illocutionary speech act is directive illocutionary speech act. Furthermore, the most widely used sentence mode is the imperative mode of the three types, namely descriptive, intogative, and imperative.Keywords: Speech Actions, Sentence Mode, Buy and Sell